Lynne Hume and Kathleen McPhillips (eds.), Popular Spiritualities: The Politics of Contemporary Enchantment. - Cusack, Carole M. (Journal for the academic study of religion, 2008)
Lynne Hume and Kathleen McPhillips (eds.), Popular Spiritualities: The Politics of Contemporary Enchantment, Ashgate, Aldershot, 2006, pp. xxii + 203, ISBN 0754639991 (hbk).